(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The causes of the occurrence and rational use of waste in the clothing industry is currently especially relevant. Inter-lunges and end waste of materials formed as a result of cutting products of the main assortment are proposed to be used for the production of goods of folk applied art.